Intrapericardial diaphragmatic hernia in a 6-month-old girl: A case report and review of the literature. (2019) - Cossa, Matchecane; Robinson, Tyler D.
Highlights: Intrapericardial congenital diaphragmatic hernia (IPCDH) is extremely rare. We report the 19th case of pediatric IPCDH in a 6-month-old girl. Our case of IPCDH was successfully surgically reduced with no significant perioperative complications. Pediatric surgeons should be aware of IPCDH. Abstract: Introduction: Intrapericardial congenital diaphragmatic hernia (IPCDH) is extremely rare: only 18 cases in children have been reported in the literature since 1981. We report the 19th case of infantile IPCDH in a 6-month-old girl and compare with previous reports. Presentation of case: Our patient initially presented with four days of dyspnea and was diagnosed with CDH by preoperative radiography. She was taken to the operating room, where an IPCDH was discovered, and successfully reduced. Discussion: CDH may present with cardiopulmonary compromise, but IPCDH directly compress the heart, leading to acute or subacute heart failure. Conclusion: Pediatric surgeons should be aware of and prepared for the possibility of IPCDH when making surgical plans to correct CDH.